2008
DOI: 10.1158/1535-7163.mct-07-2312
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor effect of dsRNA-induced p21WAF1/CIP1 gene activation in human bladder cancer cells

Abstract: We recently reported that synthetic dsRNAs targeting promoter regions can induce gene expression in a phenomenon referred to as dsRNA-induced gene activation/RNA activation (RNAa) [Li et al. Proc Natl Acad Sci U S A 2006;103:17337 -42]. The present study investigates the in vitro antitumor activity RNAa can elicit through triggering the expression of cell cycle repressor protein p21 WAF1/CIP1 (p21) in human bladder cancer cells. Transfection of a 21-nucleotide dsRNA targeting the p21 promoter (dsP21) was used… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 19 publications
2
73
0
Order By: Relevance
“…We previously showed that dsP21-322 possesses in vitro antigrowth activity in T24 and J82 bladder cancer cell lines (27). In the present study, we implement a chemically-modified variant of dsP21-322 (dsP21-322-2 0 F) with improved nuclease resistance and reduced immunostimulatory activity to improve its pharmaceutical properties for in vivo application (22).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…We previously showed that dsP21-322 possesses in vitro antigrowth activity in T24 and J82 bladder cancer cell lines (27). In the present study, we implement a chemically-modified variant of dsP21-322 (dsP21-322-2 0 F) with improved nuclease resistance and reduced immunostimulatory activity to improve its pharmaceutical properties for in vivo application (22).…”
Section: Discussionmentioning
confidence: 98%
“…Earlier in vitro studies have showed that dsP21-322 also possesses growth inhibitory function in T24 and J82 bladder cancer cell lines (27). To further evaluate dsP21-322 activity in bladder cancer, we transfected KU-7 and T24-P cells with dsP21-322 for 72 hours.…”
Section: Dsp21-322 Induces P21 Expression In Human Bladder Cancer Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although RNAi is a technique widely used to suppress the expression of specific genes in a variety of studies (40)(41)(42) on different fields of molecular biology, the exact mechanisms on many aspects are not fully understood. Controversial results were reported by several laboratories (43)(44)(45). It was reported that several dsRNAs induce gene transcription in a sequence-specific manner by targeting the promoter region of various genes (44).…”
Section: Discussionmentioning
confidence: 99%
“…12 Although, recent reports have confirmed the potential tumor suppressor effect of dsRNA mediated p21 gene activation in different cancer cell lines, 3,7,13,14 none of these reports have investigated the action of dsRNA gene activation in renal cell carcinoma. Furthermore, while two of these studies have shown an increase in both early and late apoptotic cells following dsP21 transfection, 7, 15 the mechanism by which p21 leads to apoptosis is not well defined.…”
Section: Introductionmentioning
confidence: 99%